Perceptions about Eclampsia, Birth Preparedness, and Complications Readiness among Antenatal Clients Attending a Specialist Hospital in Kano, Nigeria - Umar Muhammad Lawan; Idris Usman Takai; Hamza Ishaq (Journal of Tropical Medicine)
Background. Eclampsia is a reliable indicator of poor birth preparedness and complications readiness. We determined perceptions about eclampsia, birth preparedness, and complications readiness among antenatal clients in Kano, Nigeria. Materials and Method. A cross-sectional design was used to study 250 randomly selected antenatal clients. Data was analyzed using SPSS 16.0. Result. The mean age of the respondents was 26.1 ± 6.4 years. The majority perceived that eclampsia is preventable through good ANC (76.4%) and hospital delivery (70.8%). Overall, 66.8% had good perception about eclampsia. Having at least secondary school education and multigravidity were associated with good perception about eclampsia on multivariate analysis. About a third (39.6%) of the mothers was less prepared. On binary logistic regression, good perception about eclampsia and multigravidity were associated with being very prepared for birth. Up to 37.6% were not ready for complications. Half (50.4%) knew at least three danger signs of pregnancy, and 30.0% donated blood or identified suitable blood donor. On multivariate analysis, having at least secondary school education, being very prepared for birth, and multigravidity emerged as the only predictors of the respondents’ readiness for complications. Conclusion and Recommendations. Health workers should emphasize the practicability of birth preparedness and complications readiness during ANC and in the communities, routinely review plans, and support clients meet-up challenging areas. The importance of girl-child education to at least secondary school should be buttressed.